A Belizean Education: Learning From an International Field Experience (LEARNing Landscapes, 2014)
Although field experiences may be staple features of teacher education programs, international field experiences are still growing in popularity. This is particularly true at our university, where international field experiences are still very much in their infancy. As such, this article describes a recently completed international field experience. More specifically, a selection of a pre-service teacher’s reflections—focused upon preconceptions, observations, professional change/growth, and personal change/ growth—are shared and explored. Given that international field experiences are still relatively new within many teacher education programs, and are irregularly offered or altogether absent within others, we hope that our account of learning through such an experience will prove informative and educative to others.
Keywords: teacher education; field experience; international; reflection; professional change; growth